Cointegration & Granger causality test among trade openness and economic growth in Malaysia - Zainal Abedin, Nur Fadhlina; Maamor, Selamah (2015)
Economic globalization has caused a reduction of barriers on international trade.It was believed that, the growth in trade would increase the nation’s income.Thus, this empirical study is conducted to examine the short run and long run relationship between economic growth and trade openness.Furthermore, Foreign Direct Investment (FDI) was also investigated because it was believed that openness and economic growth influenced the flow of FDI. Statistical analysis of data had been gathered from 1974 to 2010.The methodology used was multivariate Vector Autoregressive (VAR) co-integration and causality tests.The estimation results indicate that there exists one co-integrating vector.Thus, it can be concluded that there is a long run equilibrium relationship among the variables.Not only does the result from Granger causality test show the existence of bidirectional causality between economic growth and foreign direct investment, and also, unidirectional causality or trade caused economic growth in Malaysia.